Associated Factors with the Mutual Funds Growth in Pokhara Metropolis - Lamichhane , Baburam (KIC International Journal of Social Science and Management, 2024)
This study investigates the growth and development of mutual funds in Nepal, focusing on key factors influencing their success such as investor interest, market conditions, and mutual fund schemes. Employing a quantitative research approach and descriptive research design, the study aims to evaluate the relationship between these factors and explore the investment opportunities mutual funds offer. Data was collected through purposive sampling from a sample of 250 respondents. Findings reveal that most respondents perceive a positive relationship between mutual fund performance and factors like stock market trends, economic conditions, and the regulatory environment. However, opinions differ regarding the impact of interest rate fluctuations and mutual fund performance across varying market conditions. The study provides meaningful insights for investors, fund managers, policymakers, and regulators to better understand the dynamics of mutual fund growth in Nepal and enhance strategies for market development.